Prion replication environment defines the fate of prion strain adaptation. - Elizaveta Katorcha; Nuria Gonzalez-Montalban; Natallia Makarava; Gabor G Kovacs; Ilia V Baskakov (PLoS Pathogens, 2018)
The main risk of emergence of prion diseases in humans is associated with a cross-species transmission of prions of zoonotic origin. Prion transmission between species is regulated by a species barrier. Successful cross-species transmission is often accompanied by strain adaptation and result in stable changes of strain-specific disease phenotype. Amino acid sequences of host PrPC and donor PrPSc as well as strain-specific structure of PrPSc are believed to be the main factors that control species barrier and strain adaptation. Yet, despite our knowledge of the primary structures of mammalian prions, predicting the fate of prion strain adaptation is very difficult if possible at all. The current study asked the question whether changes in cofactor environment affect the fate of prions adaptation. To address this question, hamster strain 263K was propagated under normal or RNA-depleted conditions using serial Protein Misfolding Cyclic Amplification (PMCA) conducted first in mouse and then hamster substrates. We found that 263K propagated under normal conditions in mouse and then hamster substrates induced the disease phenotype similar to the original 263K. Surprisingly, 263K that propagated first in RNA-depleted mouse substrate and then normal hamster substrate produced a new disease phenotype upon serial transmission. Moreover, 263K that propagated in RNA-depleted mouse and then RNA-depleted hamster substrates failed to induce clinical diseases for three serial passages despite a gradual increase of PrPSc in animals. To summarize, depletion of RNA in prion replication reactions changed the rate of strain adaptation and the disease phenotype upon subsequent serial passaging of PMCA-derived materials in animals. The current studies suggest that replication environment plays an important role in determining the fate of prion strain adaptation.